Analisis Faktor-Faktor yang Mempengaruhi Ekspor Nonmigas Indonesia ke Amerika Serikat - Editiawarman Editiawarman; Idris Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study examines the analysis of factors affecting Indonesian Non-oil and gas exports to America and the data used in this study are quarterly time series data from 2007Q1-2018Q. And the model used in this study is Error Correction Model. Data sourced from the World Bank and the Ministry of Trade. The results of this study are that (1) the economic growth of the United States in the long term and short term has a significant positive effect on Indonesian non-oil and gas exports to the United States (2) The exchange rate in the long term has a significant positive effect and the short term has a significant effect negative to Indonesian non-oil and gas exports to the United States (3) Foreign direct investment in the long term has a significant positive effect and in the short term does not have a significant and positive effect on Indonesian non-oil and gas exports to the United States (4) Openness of the Indonesian economy has insignificant and negative influence on non-oil and gas exports both long term and short term.